PENGARUH DISIPLIN KERJA, MOTIVASI, DAN IKLIM KERJA TERHADAP KINERJA GURU DI SMK NEGERI X PEKANBARU - Indriani, Lia; Machasin; Tarigan, Mida Aprilina (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This study aims to see the Influence of Work Discipline, Motivation, and Work Climate on Teacher Performance at SMK Negeri X Pekanbaru. The population in this study were all civil servant teachers at SMK Negeri X Pekanbaru. The sampling technique used was saturated sampling, which is a sampling technique when all members of the population are used as samples. The sample used was 46 civil servant teachers at SMK Negeri X Pekanbaru. The data analysis method used was multiple linear regression analysis using the SPSS Version 26 program. The results of the study showed that 1) work discipline had a positive and significant effect on teacher performance, 2) motivation had a positive and significant effect on teacher performance, 3) work climate had a positive and significant effect on teacher performance, 4) work discipline, motivation, and work climate together had a positive and significant effect on teacher performance.